Evaluasi Program Peningkatan Kualitas Sumber Daya Manusia Aparatur di Satuan Polisi Pamong Praja Kota Tanjungpinang - Fitria Monalisa; Fitri Kurnianingsih; Firman Firman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The problems that will be discussed in this final project are; 1. What is the form of the HR improvement program for the Apparatus at the Tanjungpinang City Satpol PP. 2. Has the program been effective in achieving the expected goals and objectives? Objectives, namely; 1. To find out the form of the HR improvement program at the Tanjungpinang City Satpol PP. 2. To find out how effective the human resource improvement program of the Tanjungpinang City Satpol PP is and to determine the success rate of the program in achieving its goals and objectives. HR development is very important to increase the effectiveness of the Tanjungpinang City Satpol PP program. This program is implemented to improve the ability and skills of Satpol PP personnel in carrying out their duties and functions. This HR improvement program consists of education and training for state defense cadres, disaster task force training, music corps guidance, PPNS and Intel training and martial arts training. This research uses a qualitative approach with descriptive methods. Data were collected through in-depth interviews and observations. The results of this study indicate that the skills, knowledge, and professionalism of Satpol PP members have been improved through these programs, which directly improve performance in maintaining public order and security. The human resource improvement program at Satpol PP Tanjungpinang City has been running effectively although there are constraints related to budget limitations.